Mobile tour guide application with on-site augmented reality - Kampar churches - Ooi, Zheng Yee (2024)
It has been demonstrated in the tourism industry that locating and highlighting interesting sites and places of interest for visitors, particularly through AR technologies, improves the overall visiting experience when they are on-site. AR-based tour guides allow travellers to have intuitive and realistic encounters. It is important to optimise tourism in Kampar so that information technology may benefit visitors and offer novel travel experiences. In general, visitors want to learn about visiting tourist attractions in an appealing way. Nowadays, it is uncommon to find mobile-based application programs that provide information about tourist attractions in Kampar. Therefore, it is crucial to create an application for providing information about tourist attractions, particularly Kampar's churches. The application uses augmented reality technology, which is expanding quickly around the globe, to display historical media about the churches. Using an Android smartphone scan a certain object or location, the software can then display pertinent media and historical data about such tourist attractions by using machine learning. As a result, augmented reality has the potential to be a new kind of advertising for the tourism industry and to boost tourism in Kampar. The project will concentrate on Sacred Heart Church, the only churches that are historically more significant than other modern churches.